ANALISIS KEMAMPUAN MENULIS PANTUN SISWA KELAS IV SD NEGERI 187 PEKANBARU - Putri Yani; Otang Kurniaman; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the problem of fourth grade students in writing a poem. In writing the students are often wrong to write a poem. Only a few students were able to write a poem in accordance with the provisions. Some students have a mistake in writing the poem, it seemed that the criteria in writing comprehension such as the number of lines in one stanza, number of syllables, prosody and terms of use of the word in the poem of sampiran and content. It found often in learning to write a poem in the school. This study aimed to describe the ability of fourth grade students of SD Negeri 187 Pekanbaru in writing a poem. This research is a descriptive quantitative research methods with the subject of this research consisted of 38 students. The data collection techniques were used technique tests. The research instrument was given the test in writing a poem with two themes specified is religion theme and social theme. Based on the research, there were 24 students got excellent category 63.16%, both categories got 13,16% consist of 5 students, 4 students got 10,52% the medium category, and the poor category were 5 students got 13,16%. Overall, the ability of students got the average score is 88 with the very good category. This suggested that the ability of fourth grade students of SD Negeri 187 Pekanbaru is very good in writing a poem.Key Words: Ability, poem